Optimizing of stud configuration on soccer boot: a finite element method - Nurul Jasmie, Che Ahamed (2013)
Soccer is one of the famous game in the world and has different boot design for related game. Many design of boot in market that has many functions for every boot. The objectives of this study are to investigate the different materials and designs of stud and to analyze the stud configuration. The materials of the stud between metal and rubber points in the bottom of soccer boot. Three types of football shoes have used to finish this project that are rounded, blade and combination of rounded and blade. The method uses during this research that experiment on force plate and simulation using ALGOR. This study focused on different material on the stud designs which are thermo polyurethane and metal. The design of the stud are rounded, blade and combination rounded and blade using Solidwork. The numbers of stud configuration are 12, 13, and 14. The design from Solidwork based on the already design in laboratory. The result value 977 N/m^2 showed the lower stress on the blade design with number of stud is 12. Based on the result, blade design is the higher stud traction due to the lower stress result than the other two design.